Analysis of Training, Self-Efficacy, and Discipline on Employee Performance Mediated by Employee Engagement: A Study in Freight Forwarding - Susanto, Primadi Candra; Murdiono, Jatmiko; Susita, Dewi (Kuras Institute, 2025)
This research aims to see the influences that cause increased performance. The research method used is Quantitative Descriptive. The data used is primary data, obtained from a questionnaire instrument with a Likert scale measurement scale of 1-5 (strongly disagree-strongly agree), filled in by employees at 6 freight forwarding companies in Jakarta, Indonesia. The sampling technique used purposive sampling with a sample size of 108 participants. The analysis software utilized is SmartPLS 4.1.0.0. The results are: 1) Training and self-efficacy have a positive and significant effect on employee engagement; 2) Discipline has no positive and insignificant effect on employee engagement; 3) Training has a positive and significant effect on employee performance; 4) Self-efficacy and discipline have no positive and insignificant effect on employee performance; 5) Employee engagement has a positive and significant effect on employee performance; 6) Training and self-efficacy have a positive and significant effect on employee performance throughout the employee's existence; and 7) Discipline has no positive and insignificant effect on employee performance through the presence of employees. To improve employee performance, it is supported by providing continuous training